Astaxanthin improves assisted reproductive technology outcomes in poor ovarian responders through alleviating oxidative stress, inflammation, and apoptosis: a randomized clinical trial - Anahid Shafie; Ashraf Aleyasin; Mojtaba Saffari; Mojtaba Saedi; Sahar Rostami; Saeede Rezayi; Seyed Danial Mohammadi; Fardin Amidi (BMC, 2024)
Abstract Background Poor ovarian response (POR) to controlled ovarian stimulation (COS) remains challenging, especially in advanced-age women with diminished ovarian reserve, resulting in low live birth rates. Many patients prefer to conceive with their eggs, underscoring the need for improved treatments. This study explores astaxanthin potential as a COS adjuvant to improve ovarian response and assisted reproductive technology (ART) outcomes, considering its impact on oxidative stress (OS), inflammation, and apoptosis, which are key factors in POR. Methods In this randomized, triple-blind, placebo-controlled trial, 60 infertile POR patients from POSEIDON Group 4 (the poorest prognosis category, age > 35 and poor ovarian reserve (anti-müllerian hormone < 1.2 ng/ml or antral follicle count < 5) undergoing intracytoplasmic sperm injection were enrolled. Patients were assigned to receive either 12 mg/day AST or placebo for eight weeks. All patients underwent a gonadotropin-releasing hormone antagonist regimen for COS. ART outcomes were compared between groups. Blood serum and follicular fluid (FF) were analyzed for OS markers (superoxide dismutase [SOD], total antioxidant capacity [TAC], and malondialdehyde [MDA]), and pro-inflammatory cytokines (interleukin-6 [IL-6], interleukin-8 [IL-8], and vascular endothelial growth factor [VEGF]) via enzyme-linked immunosorbent assay kits, and cell-free DNA [cfDNA] (apoptotic marker) via ALU quantitative polymerase chain reaction. Results After the intervention, the AST group exhibited a significant elevation in serum (P = 0.013) and TAC (P = 0.030), accompanied by a significant reduction in serum MDA (P = 0.005). No significant differences between AST and placebo groups were observed in OS markers in FF. AST group showed significant reductions in the serum IL-6 (P < 0.001), IL-8 (P = 0.001), and VEGF (P = 0.002) levels following AST therapy. In the AST group, FF levels of IL-6 (P = 0 < 001), IL-8 (P = 0.036), VEGF (P = 0.006), and cfDNA (P < 0.001) were significantly lower than in the placebo group. Between-group comparisons showed significant differences in the alterations of serum SOD (P = 0.027), IL-6 (P < 0.001), and IL-8 (P = 0.035) levels between AST and placebo groups. The AST group showed significant increases in the number of retrieved oocytes (P = 0.003), MII oocytes (P = 0.004), frozen embryos (P = 0.037), and high-quality embryos (P = 0.014) compared to the placebo group. Conclusion AST shows promise as a COS adjuvant therapy, potentially enhancing some ART outcomes in POR through alleviating OS, inflammation, and apoptosis. Trial registration Clinical trial registration number: IRCT20230223057510N1, URL: https://irct.behdasht.gov.ir/trial/68870 , registration date: 2023 March 16. Graphical Abstract